Nilai Kepemimpinan dalam Hikayat Raja Nadhir Syah: Sebuah Kajian Semiotik: Leadership Values in the Hikayat Raja Nadhir Syah: a Semiotic Study - Muwafaqoh Ni'amillah (TOTOBUANG, 2022)
Hikayat Raja Nadhir Syah is an ancient manuscript that is stored in the collection of the French National Library with the code Malayo Polynesian 62. This manuscript contains the story of the leadership of a great king. Leadership is the main key in running the wheels of government well. Ironically, Indonesia, which has been independent for 76 years, is currently facing an acute leadership crisis. Therefore, the study of the manuscript entitled Hikayat Raja Nadhir Syah is urgent. The method used in this research is qualitative. In addition, to get good and correct edits, the critical edition method is used. Then the edits are analyzed using a semiotic approach. The results of the analysis show that there are many uses of symbols contained in the Hikayat Raja Nadhir Syah text. Therefore, the disclosure of the meaning of these symbols can be used as a source of inspiration for solving the leadership crisis in this country. Keywords: Manuscripts, Hikayat Raja Nadir Shah, philology, leadership crisis